Item response theory analysis of daytime sleepiness as a symptom of obstructive sleep apnea - Gustaf J. Wellhagen; Mats O. Karlsson; Maria C. Kjellsson; Dirk Garmann; Astrid Bröker; Yang Zhang; Mika Nokela; Gerrit Weimann; Ashraf Yassen (CPT: Pharmacometrics & Systems Pharmacology)
Abstract Obstructive sleep apnea (OSA) is a sleep disorder which is linked to many health risks. The gold standard to evaluate OSA in clinical trials is the Apnea‐Hypopnea Index (AHI). However, it is time‐consuming, costly, and disregards aspects such as quality of life. Therefore, it is of interest to use patient‐reported outcomes like the Epworth Sleepiness Scale (ESS), which measures daytime sleepiness, as surrogate end points. We investigate the link between AHI and ESS, via item response theory (IRT) modeling. Through the developed IRT model it was identified that AHI and ESS are not correlated to any high degree and probably not measuring the same sleepiness construct. No covariate relationships of clinical relevance were found. This suggests that ESS is a poor choice as an end point for clinical development if treatment is targeted at improving AHI, and especially so in a mild OSA patient group.